Hubungan Jarak Kehamilan, Dukungan Suami, dan Dukungan Petugas Pelayanan KB dengan Pemilihan Metode Kontrasepsi Jangka Panjang (MKJP) di PMB Fauziah Palembang Tahun 2021 - Yuliana Yuliana; Rohaya Rohaya; Merisa Riski (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Long Term Contraception Method is a contraceptive method with long and high effectiveness. LTCM includes IUD, Implant, MOP and MOW. Based on the initial survey conducted at PMB Fauziah, Palembang City by interviewing PMB leaders, it was found that there was a lack of interest in LTCM users in the PMB. The number of active family planning acceptors in 2021 in January–June was 1,176. The purpose of the study was to determine the relationship between pregnancy distance, husband's support, support from family planning service officers in the selection of long-term contraceptive methods at PMB Fauziah Palembang in 2021. The type of research used in this study was quantitative research. The population in this study were all active family planning acceptors who visited PMB Fauziah from January-June 2021 totaling 1,176 acceptors, the research sample was 97 acceptors taken by accidental sampling technique. Data analysis in this study used univariate and bivariate analysis. The results of this study indicate the variables that have a relationship with the selection of LTCM pregnancy distance (pvalue = 0.000), husband's support (pvalue = 0.000), support from family planning service officers (p-value = 0.000). The conclusion of this study is that there is a relationship between pregnancy distance, husband's support, support family planning service officers in the selection of MKJP. The results of this study can be used as input in improving counseling methods for family planning acceptors, especially in the selection of LTCM.